Not only manganese, but fruit component effects dictate the efficiency of fruit juice as an oral magnetic resonance imaging contrast agent. (30th September 2021) - Licciardi, Giulia; Rizzo, Domenico; Ravera, Enrico; Fragai, Marco; Parigi, Giacomo; Luchinat, Claudio
Abstract : Several fruit juices are used as oral contrast agents to improve the quality of images in magnetic resonance cholangiopancreatography. They are often preferred to conventional synthetic contrast agents because of their very low cost, natural origin, intrinsic safety, and comparable image qualities. Pineapple and blueberry juices are the most employed in clinical practice due to their higher content of manganese(II) ions. The interest of pharmaceutical companies in these products is testified by the appearance in the market of fruit juice derivatives with improved contrast efficacy. Here, we investigate the origin of the contrast of blueberry juice, analyze the parameters that can effect it, and elucidate the differences with pineapple juice and manganese(II) solutions. It appears that, although manganese(II) is the paramagnetic ion responsible for the contrast, it is the interaction of manganese(II) with other juice components that modulates the efficiency of the juice as a magnetic resonance contrast agent. On these grounds, we conclude that blueberry juice concentrated to the same manganese concentration of pineapple juice would prove a more efficient contrast agent than pineapple juice. Abstract : Fruit juices with a high manganese(II) content are used as oral contrast agents for magnetic resonance imaging. NMR relaxometry shows that the juice efficiency largely depends on the matrix composition, and that blueberry juice enriched in manganese would prove a more efficient contrast agent than pineapple juice.